A Challenge for Public Universities: From Information to Communication - Sandoval, Carlos (2002)
"Globalization" is perhaps the most cited word by politicians and intellectuals in recent years. In this scenario, it is difficult to avoid platitudes. That is why this invitation is particularly difficult. I will try to elaborate on a few ideas about some of the multiple relationships between globalization, public universities, and communication. I would like to organize my participation around three themes.